Analysis of Electrical Energy the Effect of Using a Smartphone-Based Water Pump Control System Controller (Case Study of Yulihamri's Rent at Merak Sakti Road) - Antonius Rajagukguk; Iman Sahrobi Tambunan; Anhar Anhar; Alfian Ma'arif (Universitas Ahmad Dahlan, 2022)
The development of science and technology will increasingly have an impact on human life, especially electronic devices at home. In-home reservoirs, commonly, the owner of the water pump cannot detect the level of the water reservoir in his house due to no automation in the water pump. This study seeks to design a device that can control one water pump for filling three reservoirs, where the reservoir filling path will be regulated by a solenoid valve. It also aims to increase the efficiency of electrical energy in the water pump and be monitored by homeowners. The research was conducted at Yulihamri's rented house on Merak Sakti Road. In testing the measurement of electrical energy without using a control, the results obtained in the first reservoir of 1253.99 Wh, 2072.83 Wh, and 2136.27 Wh in the first, second, and third reservoirs, respectively. Meanwhile, in testing the measurement of electrical energy using the control system, the results obtained on all reservoirs in sequence are 1234.70 Wh, 1754.52 Wh, and 1644.12 Wh. The electric energy efficiency of the water pump after using the control system enhance by 15%. The contribution of this research is to reduce the use of excessive electrical energy due to the filling of water that exceeds the storage capacity so as to make it inefficient for the use of electrical energy as well as the water released. The research also limits the use of electrical energy at the end of the month, which makes this system more efficient compared to other systems.